Perancangan User Interface Aplikasi E-Nelayan Berbasis Mobile Menggunakan Metode Design Sprint - Vanda Fransiska Armanda Sari; Yekti Asmoro Kanthi; Saiful Yahya (LPPM STIKI Malang, 2022)
Dissemination of marine information such as weather and potential fish locations by the Surabaya City Marine and Fisheries Service which is still carried out conventionally indirectly so far has greatly hampered the performance of fishermen, especially in Bulak sub-district. Based on the results of the interview, one of the fishermen explained that the Bulak sub-district is a capture fisheries area that is still quite potential but the success rate of their capture fisheries business is highly dependent on marine information sources from the local government. The design of the E-Fishermen application aims to provide services in the form of a marine information system specifically for the Surabaya area. With the E-Fishermen application, all information dissemination activities will be more flexible because it can be done anytime and anywhere. The method used in designing the user interface of the E-Fishermen application is a design sprint consisting of the stages of understanding, divergence, decide, prototype and validate.